Scoping out emerging communities of practice of translation in development work in Vietnam: Empirical evidence from the perspective of Translation Studies - Nguyen Nguyen (JoSTrans: The Journal of Specialised Translation)
Despite growing attention being given to the importance of translation in development work in both Translation Studies (TS) and Development Studies (DS), relatively little has been written about the practice of translation being carried out by development workers. Focusing on the particular context of Vietnam, this study is among the first attempts to investigate how translation occurs as a shared practice in emerging communities of practice (CoPs; singular CoP) of translation there. It specifically seeks to answer two research questions: (1) What translation-related and terminology problems do development workers in Vietnam face; (2) what is the current evidence for CoPs of development workers engaging in translation in Vietnam? The study reports the results of a corpus-based textual analysis of development-related documentation, which isolated the development concept of resilience as a case study. Findings from this case study provide empirical evidence of problematic translations of development terminology and suggest the emergence of potential CoPs (Wenger 1998; Fox 2000). It is argued that the knowledge developed in TS about terminology work, corpus tools, and empirical approaches may contribute to DS.